Rapid Application Development with Mozilla™ - McFarlane, Nigel (Pearson, 2003)
Rapid Application Development with Mozilla, part of the Bruce Perens Open Source Series, is a concise guide for any programmer who wants to learn the versatility and compatibility of Mozilla, an open source toolset with over a thousand objects and components. An additional feature of Rapid Application Development with Mozilla is the NoteTaker Web browser add-on-a sample Mozilla application that is developed throughout the book. Written by Web and XML expert Nigel McFarlane, this book is the perfect addition to the library of any user-interface software engineer, cross-platform developer, or any programmer looking to discover the benefits of rapid application development.